Fundamentals of international financial accounting and reporting - Hussey, Roger (London : World Scientific, 2011)
Begins with an introduction to accounting and financial reporting, followed by a description of the development of international standards and the present structure, role and operations of the International Accounting Standards Board. This title includes a discussion on individual IFRS (International Financial Reporting Standards)
1. Accounting assumptions and facts -- 2. The growth of standard setting and the international accounting standards board -- 3. The basic of the statement of income -- 4. The basics of the statement of financial position -- 5. The basic of the statement of cash flows -- 6. Intangible assets and impairment of assets -- 7. Accounting policies, errors, provisions and contingencies -- 8. Leases, employee benefits and Texas -- 9. Financial instruments and share-based payment -- 10. Business combinations and consolidated financial statements -- 11. Specific industries and practices -- 12. Presentational issues -- 13. Foreign operations and segmental reporting -- 14. Evaluating IFRS financial statements
Includex index
Keywords: Accounting; Accounting -- Standards